2015
DOI: 10.1056/nejmoa1412082
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab in Previously Untreated Melanoma withoutBRAFMutation

Abstract: Nivolumab was associated with significant improvements in overall survival and progression-free survival, as compared with dacarbazine, among previously untreated patients who had metastatic melanoma without a BRAF mutation. (Funded by Bristol-Myers Squibb; CheckMate 066 ClinicalTrials.gov number, NCT01721772.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

71
3,630
17
119

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 4,966 publications
(3,837 citation statements)
references
References 23 publications
71
3,630
17
119
Order By: Relevance
“…110 Given the ubiquitous use of corticosteroids in the medical management of cancer patients and their immunosuppressive effects, this study primarily sought to determine whether responses mediated by anti-PD-1 therapy are influenced by corticosteroids in a preclinical setting. Utilizing well-established in vivo tumor models that are sensitive to PD-1 blockade, this study examined whether dexamethasone’s impact was dependent on its timing, duration, and tumor location within or outside the CNS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…110 Given the ubiquitous use of corticosteroids in the medical management of cancer patients and their immunosuppressive effects, this study primarily sought to determine whether responses mediated by anti-PD-1 therapy are influenced by corticosteroids in a preclinical setting. Utilizing well-established in vivo tumor models that are sensitive to PD-1 blockade, this study examined whether dexamethasone’s impact was dependent on its timing, duration, and tumor location within or outside the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…110 As the list of approvals and clinical trials investigating its efficacy in other tumor types continues to grow, it is paramount to determine factors, both tumor-intrinsic and extrinsic, that influence responses to anti-PD-1 therapy. 11 An important concern to address is how iatrogenic immunosuppression caused by conventional therapies such as chemotherapy, fractionated radiotherapy, and corticosteroids may potentially impact the efficacy of anti-PD-1 as well as other immunotherapy strategies.…”
Section: Introductionmentioning
confidence: 99%
“…However, as novel agents extend patient survival times, it becomes increasingly difficult to conduct long clinical trials in order to measure OS [75,76]. Although the use of ICBs has improved survival in melanoma over standard chemotherapy, with some patients experiencing OS of 3 to 5 years [77,78], when the follow-up is less than 1 year, median OS is usually not reached [22,23,39,43]. Therefore, there is an interest in validating surrogate endpoints that can accurately predict survival benefit in clinical trials of immunotherapy and using these surrogate endpoints for drug approval [75].…”
Section: Endpoints To Assess Clinical Outcomes Associated With Icbsmentioning
confidence: 99%
“…Some studies investigating ICBs in NSCLC, RCC, HNSCC, and UC have demonstrated increased OS in the absence of a PFS benefit [27,28,31,42,47,57], whereas other trials in melanoma and NSCLC have demonstrated increased OS, as well as ORR and PFS, compared with standard of care (Table 2) [23,43].…”
Section: Endpoints To Assess Clinical Outcomes Associated With Icbsmentioning
confidence: 99%
See 1 more Smart Citation